2020
DOI: 10.1177/2235042x20981190
|View full text |Cite
|
Sign up to set email alerts
|

The complexity of caregiving for community-living older adults with multiple chronic conditions: A qualitative study

Abstract: Background: Older adults with multiple chronic conditions (MCC) rely heavily on caregivers for assistance with care. However, we know little about their psychosocial experiences and their needs for support in managing MCC. The purpose of this study was to explore the experiences of caregivers of older adults living in the community with MCC. Methods: This qualitative study was a secondary analysis of previously collected data from caregivers in Ontario and Alberta, Canada. Participants included caregivers of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 56 publications
5
21
0
Order By: Relevance
“…Our results revealed that caregivers of people with combined brain health and physical health conditions were the most burdened and had the highest levels of loneliness and social isolation. This finding supports our first hypothesis and extends previous findings that caregivers of people with more severe conditions and those with multimorbidity experience higher levels of stress, anxiety, and depression, [56][57][58] as well as previous findings of high burden in caregivers of people with neurodegenerative conditions, prepandemic. 4,5,16,34,40,42,59,60 Outcomes of caregivers of people with dementia and other enduring brain health conditions are often worse compared to caregivers who care for people with physical disabilities alone or who are older and frail.…”
Section: Discussionsupporting
confidence: 92%
“…Our results revealed that caregivers of people with combined brain health and physical health conditions were the most burdened and had the highest levels of loneliness and social isolation. This finding supports our first hypothesis and extends previous findings that caregivers of people with more severe conditions and those with multimorbidity experience higher levels of stress, anxiety, and depression, [56][57][58] as well as previous findings of high burden in caregivers of people with neurodegenerative conditions, prepandemic. 4,5,16,34,40,42,59,60 Outcomes of caregivers of people with dementia and other enduring brain health conditions are often worse compared to caregivers who care for people with physical disabilities alone or who are older and frail.…”
Section: Discussionsupporting
confidence: 92%
“…The support provided by these informal caregivers is often crucial for enabling older adults to safely remain in their home environment [ 2 - 4 ]. Caregiving support, such as assistance with activities of daily living, attending appointments, and health management, is associated with positive outcomes for both caregivers [ 5 , 6 ] and care recipients [ 7 ]. Although caregivers often willingly engage in caring, their role can negatively affect their psychological well-being, particularly when care is provided over a prolonged period [ 8 - 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the deepening of aging population degree, long-term care for disabled elderly has become a challenging problem gradually. On the one hand, the disabled elderly hope to stay at home [11]; Nevertheless, due to the weakening of family function and the limited support family providing [10], it is di cult to fully realize the home-based long-term care for the disabled elderly, which eventually leads to the increasing demand for community care [21] .…”
Section: Discussionmentioning
confidence: 99%